Perbandingan Pemeriksaan Leukosit Urine Segar Dengan Setelah 2 Jam Di Suhu Kamar - Nur Vita Purwaningsih (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2018)
ABSTRACTBackground: Urinalysis is a parameter often requested by clinicians. The urinalysis parameters consist of macroscopic, microscopic or sedimental examination and urine chemistry examination. Urine examination is very important, especially in making the diagnosis. Procrastination delay results in errors in diagnosis and administration of drugs that lead to adverse outcomes of patients, analysis should be performed no later than 4 hours after sampling. Urine has a stability at room temperature ie for 1 hour, if urine is silenced long then the bacteria will multiply, so it can decompose NH3 (ammonia) which is alkaline. Under alkaline conditions, the pH in the urine will increase. This may affect the sediment component in the urine to rapid lysis so that the amount will be reduced General purpose of this study to determine the difference results of examination of fresh urine leukocytes compared after 2 hours at room temperature. Method: descriptive observasional with number of sample counted 20 sample. Result: Based on the test result, the positive percentage value in fresh urine is 100% and the positive percentage value in urine after 2 hours is 70%. In the Wilcoxon statistical test obtained p-value <0.001 (> 0.05). Conclusion: Based on the research that has been done then it can be concluded that there are differences in the results of fresh urine leukosit better than urine after 2 hours at room temperature.Keywords: Leukocyte urine, Fresh urine, delay.